2014
DOI: 10.1177/028072701403200304
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Psychosocial Decision Making in Emergency Operations Centres

Abstract: The researchers compared the effectiveness of two decision models for modeling decision making in Emergency Operations Centers (EOCs): Klein's Recognition Primed Decision (RPD) model and Gladwin's Ethnographic Decision Tree Model (EDTM). The focus was on decisions that affect the psychological and social well-being of responders and community members. Communities of EOC personnel participated in a simulated emergency event, followed by an interview and/or focus group. Analysis of the decision-making processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…During training for the EOC participants were told that first responders were the highest priority for the EOC; however, no participant reported that event in a sitrep. This is in accord with the findings of Javor et al (2014), who found that even trained EOC personnel and first responders also neglected to acknowledge this event, partially due to the lack of dedicated psychosocial support and training for EOC staff managing disaster events.…”
Section: Significant Events That Were Not Mentionedsupporting
confidence: 88%
See 4 more Smart Citations
“…During training for the EOC participants were told that first responders were the highest priority for the EOC; however, no participant reported that event in a sitrep. This is in accord with the findings of Javor et al (2014), who found that even trained EOC personnel and first responders also neglected to acknowledge this event, partially due to the lack of dedicated psychosocial support and training for EOC staff managing disaster events.…”
Section: Significant Events That Were Not Mentionedsupporting
confidence: 88%
“…One study involved a hospital emergency department staff, consisting of nurses, technicians, emergency medicine residents, and attending physicians and focused on group dynamics rather than individual roles (Shapiro et al 2004). Another, more recent study of EOC behaviors (Javor et al 2014) used a simulation of an extreme winter storm in a fictional city called Denton to study psychosocial decision-making in EOCs in crises. In particular, the emphasis of their experimental manipulation was upon the ability of team members to cope with behavioral issues that may emerge because of stress in the EOC.…”
Section: Prior Studies the Experimental Framework Andmentioning
confidence: 99%
See 3 more Smart Citations